60 YEARS OF POMC: Transcriptional and epigenetic regulation of POMC gene expression. (May 2016) - Drouin, Jacques
Abstract : Expression of the pro-opiomelanocortin ( POMC ) gene integrates numerous inputs that reflect the developmental history of POMC-expressing cells of the pituitary and hypothalamus, as well as their critical role in the endocrine system. These inputs are integrated at specific regulatory sequences within the promoter and pituitary or hypothalamic enhancers of the POMC locus. Investigations of developmental mechanisms and transcription factors (TFs) responsible for pituitary activation of POMC transcription led to the discovery of the Pitx factors that have critical roles in pituitary development and striking patterning functions in embryonic development. Terminal differentiation of the two pituitary POMC lineages, the corticotrophs and melanotrophs, is controlled by Tpit; mutations of the human TPIT gene cause isolated adrenocorticotrophic hormone deficiency. Intermediate lobe and melanotroph identity is provided by the pioneer TF Pax7 that remodels chromatin to reveal a new repertoire of enhancers for Tpit action. Many signaling pathways regulate POMC transcription including activation by hypothalamic corticotrophin-releasing hormone acting through the orphan nuclear receptors of the Nur family and feedback repression by glucocorticoids and their glucocorticoid receptor. TFs of the basic helix-loop-helix, Smad, Stat, Etv, and nuclear factor-B families also mediate signals for control of POMC transcription. Whereas most of these regulatory processes are conserved in different species, there are also notable differences between specific targets for regulation of the human compared with mouse POMC genes.